Pulse properties of terrestrial gamma‐ray flashes detected by the Fermi Gamma‐Ray Burst Monitor. Issue 7 (24th July 2014) - Foley, S.; Fitzpatrick, G.; Briggs, M. S.; Connaughton, V.; Tierney, D.; McBreen, S.; Dwyer, J. R.; Chaplin, V. L.; Bhat, P. N.; Byrne, D.; Cramer, E.; Fishman, G. J.; et al.
Abstract The Gamma‐ray Burst Monitor (GBM) on board the Fermi Gamma‐ray Space Telescope has triggered on over 300 terrestrial gamma‐ray flashes (TGFs) since its launch in June 2008. With 14 detectors, GBM collects on average ∼100 counts per triggered TGF, enabling unprecedented studies of the time profiles of TGFs. Here we present the first rigorous analysis of the temporal properties of a large sample of TGFs (278), including the distributions of the rise and fall times of the individual pulses and their durations. A variety of time profiles are observed with 19% of TGFs having multiple pulses separated in time and 31 clear cases of partially overlapping pulses. The effect of instrumental dead time and pulse pileup on the temporal properties are also presented. As the observed gamma ray pulse structure is representative of the electron flux at the source, TGF pulse parameters are critical to distinguish between relativistic feedback discharge and lightning leader models. We show that at least 67% of TGFs at satellite altitudes are significantly asymmetric. For the asymmetric pulses, the rise times are almost always shorter than the fall times. Those which are not are consistent with statistical fluctuations. The median rise time for asymmetric pulses is ∼3 times shorter than for symmetric pulses while their fall times are comparable. The asymmetric shapes observed are consistent with the relativistic feedback discharge model when Compton scattering of photons between the source and Fermi is included, and instrumental effects are taken into account.